The Influence of Tax Knowledge, Tax Socialization, and Fiscal Services on Tax Compliance of Individual Taxpayers with The Voluntary Disclosure Program as a Moderation Variable: Empirical Study on Individual Taxpayers in the KPP Pratama Jakarta Sawah Besar Dua Area - Yanti, Dilla Madi; Subiyanto, Bambang; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This research aims to analyze the influence of tax knowledge, tax socialization, and tax authorities' services on tax compliance of Individual Taxpayers with the Voluntary Disclosure Program (PPS) as a study moderating variable for Individual Taxpayers in the KPP Pratama Jakarta Sawah Besar Dua Area. This research approach uses primary data through distributing questionnaires. The sampling technique was 100 respondents—technical data analysis using Partial Least Squares (PLS) with the SmartPLS version 3.0 program. The results of the research show that the tax knowledge variable has a significant negative effect on individual taxpayers' tax compliance, the socialization variable has a significant positive effect on individual taxpayers' tax compliance, tax authorities' services have a significant effect on individual taxpayers' tax compliance, PPS can moderate the effect of tax knowledge on individual taxpayers. Individual Taxpayer tax compliance, PPS is unable to moderate the influence of tax socialization on Individual Taxpayer compliance, and PPS can moderate the influence of tax authorities services on Individual Taxpayer tax compliance.